Siber Uzayın Küresel Sisteme Etkileri - UÇ, Furkan Batuhan (Cyberpolitik Journal, 2023)
This study mainly focuses on the effects of cyber space and accompanying cyber technologies, which have entered the life of humanity in the last thirty years, expanding and deepening its place in our lives and creating an information or information age, on the global system, where not only the external but also the internal sovereignty of the states is somewhat limited. First of all, the great social and political changes and transformations caused by the information revolutions since the 15th century were mentioned. Afterwards, the effects of the information age on the formation of a new global system were discussed with the perspectives of the theories of the discipline of International Relations. In this section, the perspectives of realism, liberalism and constructivism are discussed separately. On the other hand, the innovation that cyber technologies cause in the concept of national security, which limits the sovereignty and control of states to a great extent, has been examined. Thirdly, it is mentioned that it provides an opportunity for the formation of new cyber communities, that individuals can gather and organize faster, and that these virtual organizations can be reflected in our physical lives as protests. Fourth, the benefits it provides to non-state actors and the consequent erosion of the sovereignty of states were examined. Finally, in the face of the positive and negative developments that the cyber universe may create, a utopian and partly dystopian future has been tried to be imagined.